Cognitive Processes in Translation: A Systematic Review of Novice Translators’ Strategies and Research Trends - Roswani Siregar; Heni Subagiharti; Diah Syafitri Handayani; Dermawan Hutagaol; Efendi Barus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study examines cognitive processes in translation with a particular focus on novice translators through a systematic literature review. The objectives are to identify the main cognitive stages in translation, examine cognitive and metacognitive strategies used by novice translators, analyze research methods in translation process studies, and identify research gaps for future investigation. Following the PRISMA 2020 guidelines, this review analyzes 27 peer-reviewed studies published between 2015 and 2025, sourced from Scopus, Web of Science, and Google Scholar. A thematic analysis approach was employed to classify the studies into five key themes: cognitive stages, cognitive and metacognitive strategies, novice–expert differences, research methodologies, and technology-mediated translation. The findings indicate that translation is a recursive cognitive process involving comprehension, transfer, production, and revision. Novice translators tend to rely on surface-level strategies and demonstrate limited metacognitive regulation compared to experts. Methodologically, translation process research is dominated by think-aloud protocols, supplemented by eye-tracking and keystroke logging, each with inherent limitations. In addition, the role of technology in shaping translation cognition remains relatively underexplored. This study highlights the need for integrated approaches that combine cognitive, metacognitive, and technological perspectives, and emphasizes the importance of process-oriented pedagogy in developing translation competence.